THE IMPACT OF INFLATION ON ECONOMIC DEVELOPMENT AND WAYS TO REDUCE IT: A FOCUS ON UZBEKISTAN - Akhmadjonov Odiljon (American Journals, 2024)
This article analyzes the impact of inflation on Uzbekistan's economic development, highlighting its effects on purchasing power, investment, and income distribution. It examines inflation trends, challenges, and government efforts to stabilize the economy through fiscal and monetary reforms. It concludes by emphasizing the importance of continued economic diversification and productivity growth.
Keywords: Inflation, Economic Development, Monetary Policy, Investment Climate, Economic Reforms.